2018
DOI: 10.5194/gi-7-307-2018
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of three-dimensional density tomography using dozens of muon radiographies and filtered back projection for volcanos

Abstract: Abstract. This study is the first trial to apply the method of filtered back projection (FBP) to reconstruct three-dimensional (3-D) bulk density images via cosmic-ray muons. We also simulated three-dimensional reconstruction image with dozens of muon radiographies for a volcano using the FBP method and evaluated its practicality. The FBP method is widely used in X-ray and CT image reconstruction but has not been used in the field of muon radiography. One of the merits of using the FBP method instead of the or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
(28 reference statements)
0
14
0
Order By: Relevance
“…The images revealed increased average rock densities across the east side of the activated Minamidake and underneath the deactivated Showa crater with a spatial resolution of ∼60 m. Despite the underestimated average densities due to the detection of energetic background muons, it is reasonable for us to interpret that the excessive density found in the current muographic image was produced by the formation of a volcanic plug. Multidirectional muography (Nagahara & Miyamoto, ) and its combination with high‐resolution gravity (Rosas‐Carbajal et al, ) are good candidates to achieve three‐dimensional monitoring of magma movements inside active volcanoes in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The images revealed increased average rock densities across the east side of the activated Minamidake and underneath the deactivated Showa crater with a spatial resolution of ∼60 m. Despite the underestimated average densities due to the detection of energetic background muons, it is reasonable for us to interpret that the excessive density found in the current muographic image was produced by the formation of a volcanic plug. Multidirectional muography (Nagahara & Miyamoto, ) and its combination with high‐resolution gravity (Rosas‐Carbajal et al, ) are good candidates to achieve three‐dimensional monitoring of magma movements inside active volcanoes in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Multidirectional muography (Nagahara & Miyamoto, 2018) and its combination with high-resolution gravity (Rosas-Carbajal et al, 2017) are good candidates to achieve three-dimensional monitoring of magma movements inside active volcanoes in the future.…”
Section: 1029/2019gl084784mentioning
confidence: 99%
“…A simulation study showed that at least 16 2D muon radiographic images captured from independent directions are necessary to reconstruct a 3D density model of a target with a reasonable resolution. 23) However, it is not practical to evenly distribute many muon detectors around a volcano having a rugged topography. Because long-term electric power supply is not feasible for such conditions, there is no alternative but to use the emulsion plates as muon detectors.…”
Section: Nonuniqueness Of Gravimetric Inversion For Subsurface Densitymentioning
confidence: 99%
“…Although the conduit is no longer blocked, Eqs. [19]- [23] still provide an appropriate model for computing the deformation and gravity changes during the eruption by considering negative values of "P and "V to model the deflating magma chamber. This formulation will be used to analyze the gravity change for a deflating pressure source in section 4.5.…”
Section: ½19mentioning
confidence: 99%
“…Muon tomography, consisting of combining muographies from several viewpoints, allows the reconstruction the 3-D density distribution. To conduct a muon tomography, Nagahara & Miyamoto (2018) used the method of filtered back projection, which has the advantage of not relying on any a priori information. They show that the method requires data from at least a dozen of viewpoints to allow a proper 3-D reconstruction, which is for now impractical.…”
Section: Introductionmentioning
confidence: 99%